(untitled) (Nigerian Journal of Physiological Sciences, 2019)
Diabetes mellitus is a devastating illness associated with alterations in the pancreatic islet of Langerhans and the islet volume constitutes a significant variable in diabetic investigations. This study investigates the volume of pancreatic islets in type 2 diabetic rats following treatment with aqueous extract Byrsocarpus coccineus leaves. Twenty-five male Wistar rats weighing between 100-120g were divided into five groups. Group 1 served as the normal control given distilled water while type 2 diabetes mellitus was induced by a high fat diet feeding for five weeks and a single dose of streptozotocin (35mg/kg, i.p.) in groups 2,3,4 and 5. After confirmation of diabetes, animals in groups 2,3,4 and 5 were administered normal saline, 50 mg/kg metformin, 800 mg/kg Byrsocarpus coccineus leaves leaf extract (BCLE) and 400 mg/kg BCLE respectively for 21 days. The pancreas was harvested, fixed in neutral buffered formalin and processed for stereological and histological analysis. Isotropic uniform random samples were obtained with the orientator grid. Serial sections were cut with a rotatory microtome and stained with Haematoxylin and Eosin. Pancreatic islet volumes were measured with the aid of a Cavalieri estimator grid. The result showed significant (p<0.05) increase in the blood glucose level of the diabetic control group, when compared to the normal control. But blood glucose levels from groups 4 and 5 were significantly (p<0.05) decreased when compared to the diabetic control. Pancreatic islet volume estimations showed a significant decrease in the diabetic control group when compared to the normal control (p<0.05), while pancreatic islet volumes in groups 3, 4 and 5 were significantly increased when compared to the diabetic control group (p<0.05). In a likewise manner the histology of the pancreas of the diabetic control shows damaged pancreatic islet cells and surrounding tissue that was reduced in all the treated group. In conclusion the aqueous extract of Byrsocarpus coccineus has shown an anti- hyperglycaemic effect in the experimental rats and increased the volumes of the pancreatic islet cells as well as ameliorated the pathological changes in the pancreas.